Counting Witches: Illuminating and Distorting the Shape of Witchcraft Accusations in Scotland. Issue 1 (May 2017) - Macdonald, Stuart
Abstract : Scottish historians have invested considerable effort in gathering data on and counting the number of accused witches in Scotland in the sixteenth and seventeenth centuries. The benefits of the four projects dedicated to this data-gathering that are analysed in this article are clear, but the act of counting has also changed our perception of the Scottish witch-hunt. In order to count witches, we have to have a clear definition of who is (and is not) a witch. This article explores the change in definition across these projects, notably the distinction between a witch and a charmer. Graphing witchcraft accusations gives the impression that all accusations are related. Counting may make us overconfident in the quality of the data when what is striking is how little information we have in most instances. The methodological concern of using the information we do have and interpreting the entire witch-hunt on that basis is noted.